Respuesta :
we have that
[tex] x^2 - bx + b [/tex]
we know that
If [tex] (x-2) [/tex] is a factor of [tex] x^2 - bx + b [/tex]
then
for [tex] x=2 [/tex]
[tex] x^2 - bx + b [/tex] is equal to zero
so
[tex] 2^2 - b*2 + b=0 [/tex]
[tex] 4 - 2b + b=0 [/tex]
[tex] b=4 [/tex]
therefore
the answer is
the value of b is equal to [tex] 4 [/tex]
The value of b that makes x-2 a factor of x² - bx + b is 4.
Polynomial is an expression involving the operations of addition, subtraction, multiplication of variables.
Types of polynomials are quadratic, linear, cubic and so on.
The factor theorem states that; when f(k) = 0, then (x – k) is a factor of f(x).
Given that x-2 is a factor of x² - bx + b, hence:
f(2) = 2² - b(2) + b = 0
4 - 2b + b = 0
b = 4
Therefore the value of b that makes x-2 a factor of x² - bx + b is 4.
Find out more at: https://brainly.com/question/2449381